2012
DOI: 10.1186/1471-2164-13-179
|View full text |Cite
|
Sign up to set email alerts
|

Unique core genomes of the bacterial family vibrionaceae: insights into niche adaptation and speciation

Abstract: BackgroundThe criteria for defining bacterial species and even the concept of bacterial species itself are under debate, and the discussion is apparently intensifying as more genome sequence data is becoming available. However, it is still unclear how the new advances in genomics should be used most efficiently to address this question. In this study we identify genes that are common to any group of genomes in our dataset, to determine whether genes specific to a particular taxon exist and to investigate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…For example, a recent study of unique core genomes in Vibrionaceae reported that V. cholerae and V. parahaemolyticus have 12 and 124 unique genes, respectively (Kahlke et al, 2012). A comparable number was obtained in this study for V. harveyi with 94 unique gene families (data not shown).…”
Section: Campbellii Comprises At Least Three Subspeciessupporting
confidence: 82%
See 1 more Smart Citation
“…For example, a recent study of unique core genomes in Vibrionaceae reported that V. cholerae and V. parahaemolyticus have 12 and 124 unique genes, respectively (Kahlke et al, 2012). A comparable number was obtained in this study for V. harveyi with 94 unique gene families (data not shown).…”
Section: Campbellii Comprises At Least Three Subspeciessupporting
confidence: 82%
“…The published draft genome sequences of V. harveyi CAIM 1792 and various Harveyi clade members were obtained from the NCBI organism genome INSDC database (Karsch-Mizrachi et al, 2012). Twenty-one new draft genome sequences (eleven V. harveyi, eight V. campbellii, two V. owensii, Table 1) were generated using the MiSeq Reagent kit v2 (500-cycle kit) and a MiSeq desktop sequencer (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…4A, may be used to define species. An analysis of the Vibrionaceae demonstrated that similar considerations may be used to delineate fine taxonomic relationships within a larger taxonomic group (19).…”
Section: Resultsmentioning
confidence: 99%
“…Dispensable genes in bacteria are thought to contribute to diversity and adaptation (Medini et al, 2005;Tettelin et al, 2005Tettelin et al, , 2008Kahlke et al, 2012). In plants, the timing of developmental transitions is important for evolution and adaptation to new environments; in crop species, such transitions have had an important role in crop domestication and cultivar improvement.…”
Section: Introductionmentioning
confidence: 99%